GAMBARAN SELF EFFICACY PADA PASIEN DIABETES TIPE 2 DI POLIKLINIK PENYAKIT DALAM RSUPN DR. CIPTO MANGUNKUSUMO JAKARTA - Shanty Chloranyta (Persatuan Perawat Nasional Indonesia (PPNI) Jawa Tengah, 2020)
Self-efficacy is an individual's assessment of the ability to complete a given task. Diabetes self-efficacy is required to improve the outcome of diabetes management. This study aims to assess the ability of self-efficacy in diabetic patients using Diabetes Management Self Efficacy (DMSE). The research design used is descriptive method. The study was conducted at the Internal Medicine Polyclinic of Cipto Mangunkusumo Hospital Jakarta with 60 samples of type 2 diabetes patients using consecutive sampling technique. The measuring instruments used were demographic characteristics and Diabetes Management Self Efficacy (DSME). The results showed the characteristics of the respondents in the study were 57% women, the highest education was high school respondents (33%), the most complications were diabetic retinopathy (38%). Based on the mean age of type 2 diabetes respondents, namely 57.60 years, the average length of diabetes was 11.40 years, and the mean self-efficacy score was 59.0. Assessment of self-efficacy using DMSE can be used to assess self-efficacy in type 2 diabetes, so that it can make it easier for nurses to educate and counsel patients with type 2 diabetes related to self-efficacy so that it can improve selfmanagement in type 2 diabetes patients.